FRI0381 During antisynthetase syndrome, anti-citrullinated peptides are a marker of severe joint disease. (23rd January 2014) - Meyer, A.; Lefevre, G.; Tournadre, A.; Le Goff, B.; Ottaviani, S.; Buchdahl, A.-L.; De Brandt, M.; Coquerelle, P.; Flipo, R.-M.; Falgarone, G.; Bernard, G.; Amoura, Z.; et al.
Abstract : Background: The clinical meaning of anti-citrullinated peptide antibodies (ACPA) in antisynthetase syndrome (ASS) is unknown. Methods: ASS patients with ACPA were identified among a 9 French center series of 284 patients with ASS and through declarative cases from clinicians registered on the Club Rhumatismes et Inflammation web site. ASS was defined by the presence of an antisynthetase antibody (ARS) and at least two organ involvements among interstitial lung disease (ILD) (abnormal pulmonary function tests and/or typical thoracic HRCT-scan), myositis (muscle weakness, CK level >2 times normal range, myopathic changes on EMG and/or typical features on biopsy) and typical skin manifestations. ACPA were positive when >30 IU/ml (ELISA and/or LUMINEX). Results: Eleven female and two male (median age of 43 years, range 23-57) were tested positive for ACPA (median serum amount 183 IU/ml, range 33-7742). ARS were anti-Jo1 (n=10), anti-PL7 (n=2) or anti-PL12 (n=1) and were identified concomitantly (n=10), 4 years before (n=1) or 3-6 years after (n=2) the ACPA detection. Rheumatoid factor (latex) was found in 11 patients (213 IU/L, range 16-925). Among the tested patients, HLA-DR4 allele was found in one case. All patient suffered of symetrical arthritis, involving mainly small joints of the hand (n=13) sparing distal interphalangeal (IP) joints (n=12), with 9 tender joints (range 4-24) and 5.5 swollen joints (range 2-18). The visual analogic pain scale was 60/100, ranging from 20 to 66. Bone erosions were found in 10 patients (78%), mainly on metacarpophalangeal (n=6), metatarsophalangeal (n=4), wirst (n=4) and proximal IP (n=3) joints. All patients presented with at least 2 other symptoms of ASS: - ILD (n=11), occurring prior to (n=3, 2-5 years), at the same time of (n=4) or after (n=4, 1-6 years) the detection of ACPA, with variable severity (vital capacity 94% (range 44-100) and DLCO 67 % (range 48-103). HRCT findings were systematically in accordance with non-specific interstitial pneumonia. - Myositis (n=11) was diagnosed 5-11 years before (n=3), concomitantly (n=5) and 1-3 years after (n=3) the ACPA detection. Muscle weakness was present in 10 patients and the median CK level was 1807 UI/L (range 245-11, 434). - Skin manifestations (n=9) were mechanic's hand (n=3), signs of dermatomyositis (n=4) and/or Raynaud's phenomenon (n=7) that appeared 1- 2 years before (n=3), concomitantly (n=3) or 3 years after (n=1) the detection of ACPA. All patients received corticosteroids while eleven were treated with DMARDs : methotrexate (n=11), leflunomid (n=1), plaquenil (n=1), mycophenolate mofetil (n=2), Azathioprine (n=1). Seven patients received biologics because of refractory arthritis, including rituximab (n=4), infliximab (n=3), adalimumab (n=1), etanercept (1), tocilizumab (n=1) and/or abatacept (n=1). Other treatments were intraveinous immunoglobulins (n=1) and cyclophosphamide (n=1). Conclusions: In ASS, ACPA are associated with severe and erosive arthritis, whereas the prognosis of the other specific ASS involvements seems good. Disclosure of Interest : None Declared